Monthly 90 deg N Atmospheres and High-Latitude Warm and Cold Winter Stratosphere/Mesosphere - Kantor, Arthur J; Cole, Allen E (1977)
A set of 12 mean monthly reference atmospheres, which describes the seasonal changes in the distribution of the thermodynamic properties of the atmosphere, is provided for the North Pole for altitudes up to 55 km. Additional atmospheric models for arctic and subarctic regions are presented to describe the large variations that occur in the vertical distributions of atmospheric temperature, density, and pressure during typical warmings and coolings of the winter stratosphere and mesosphere.